1998
DOI: 10.1017/s1047951100004698
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the mitral valve because of pure rheumatic mitral valvar incompetence in the young

Abstract: Between January 1985 and April 1994, 42 children aged between 7 and 14 years (mean 11.3 years) underwent repair of severely incompetent rheumatic mitral valves with no accompanying mitral stenosis. In 19 patients the tricuspid valve was severely incompetent, while 8 patients had severe aortic incompetence. Overall, the repair incorporated shortening of elongated tendinous cords and insertion of a Duran or Carpentier prosthetic ring. The repair was the sole procedure in 15 patients, whilst 19 patients also had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
4
1
1
Order By: Relevance
“…Despite relatively early attempt of valve repair in rheumatic mitral regurgitation, higher rates of failure and late re-operation compared to the degenerative mitral regurgitation group made most physicians and surgeons believe that etiology plays an important role in the results of repair (9,10,14,16). Unlike the previous clinical reports, our study shows different results of valve repair for rheumatic mitral regurgitation.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Despite relatively early attempt of valve repair in rheumatic mitral regurgitation, higher rates of failure and late re-operation compared to the degenerative mitral regurgitation group made most physicians and surgeons believe that etiology plays an important role in the results of repair (9,10,14,16). Unlike the previous clinical reports, our study shows different results of valve repair for rheumatic mitral regurgitation.…”
Section: Discussioncontrasting
confidence: 72%
“…In a few studies on predominant rheumatic mitral regurgitation, the mean age of the subjects was between 11 to 27 yr (14,15,18). Duran and other investigators reported that young age with high chance of active rheumatic carditis is an important predisposing factor of re-operation (7,8,13,14,16), which has been challenged recently by another group (18). The most important difference, we believe, is that all patients underwent preoperative echocardiographic screening for feasibility of repair surgery in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatic disease is currently known to carry a high risk of reoperation [11][12][13] compared with degenerative disease. 4,12,14 However, the global rate of reoperation is 2% patients per year.…”
Section: Discussionmentioning
confidence: 99%
“…O resultado da reconstrução mitral na doença cardíaca reumática varia na literatura, dependendo, provavelmente, do comportamento bioló-gico da doença nos diversos continentes, e da qualidade assistencial oferecida a essas populações (5)(6)(7)(8) .…”
Section: Introductionunclassified